Advances in Business and Management Forecasting. - Lawrence, Kenneth D. (Advances in business and management forecasting., 2017)
Volume 12 presents studies in the application of forecasting methodologies to such areas as supply chain, health care, prospecting for donations from university alumni, and the use of clustering and regression in forecasting. The orientation of this volume is for business applications for both the researcher and the practitioner of forecasting.